Meanings of "the existential" in a Secular Country: A Survey Study - Hvidt, Niels Christian (Journal of religion and health, 2022)
"The existential" is a concept that many people use albeit associated with different meanings. In order to increase research-based insight into the meaning of "the existential," we conducted a questionnaire study in Denmark in 2018 in which we asked 1.106 Danes of various age, gender, educational and geographical background about personal associations linked to "the existential." Factor analysis of the answers resulted in three different groups of meaning: (1) essential meanings of life, (2) spirituality/religiosity and (3) existential thinking. The findings show that "the existential" serves well as an overarching construct potentially including secular, spiritual and religious meaning domains, at least within the European context.